Environmental Marine Geoscience 1. Status and Trends of Marine High-Resolution Seismic Reflection Profiling: Data Acquistion - Mosher, David; Simpkin, Peter (Geoscience Canada, 1999)
Summary For marine high-resolution seismic reflection profiling systems, source energyis low, impedance changes are small, wide bandwiths are required, signal attenuation is high, and the seismic source, receiver and geometry are as critical to the resulting profile image as is the sub-surface geology. For geophysics to play a larger role in offshore environmental, resource and engineering assessment there is a need for improvements in resolution, quantification and consistency in the collection, processing and display of marine high-resolution seismic reflection data. This paper reviews the four broad categories of source technologies (controlled waveform, accelerating water mass, explosive and implosive), receiver geometric considerations, and discusses evolving survey and technological trends in support of marine high-resolution seismic reflection surveying.